Extraction of papain enzyme from papaya leaves using hot water extraction with ultrasonic â assisted pretreatment - Izzah Suhaila, Abu Bakar (2010)
Papaya leaf is not just a byproduct of papaya tree but it contains an essential enzyme which is papain. The aim of the study is to measure the amount of this enzyme extracted from leaf tissue using hot water extraction with ultrasonic-assisted pretreatment as well as to determine the optimum condition for the extraction process. The leaves were subjected to a pretreatment which is grinding and ultrasonication followed by hot water extraction and finally, enzymatic analysis using UV-Vis spectrophotometer. The parameters involved in the process were ultrasonication time (30 â 90 minutes) and frequency (18 â 26 kHz), solid-solvent ratio (1:5 â 1:25), and extraction time (1 â 5 hour) and temperature (50 - 70Â°C). Among these parameters, maximum concentration of papain enzyme was achieved at 60 minutes and 20 kHz of ultrasonication, solid-solvent ratio at 1:5, extraction time at 4 hours and extraction temperature at 60Â°C. In conclusion, the maximum concentration of papain enzyme achieved at this optimum parameter was 4.020 ÂµM. Utilization of PEGâphosphate system for separation and purification of papain is recommended in order to get the pure papain enzyme.